2016
DOI: 10.1590/0103-8478cr20150132
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus on performance, hematological, biochemical, and bone parameters of growing pigs

Abstract: The purpose of this study was to assess the levels of available phosphorus (AP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Previous investigations have demonstrated that phosphorus deficiency can induce a variety of functional and structural changes such as muscle weakness, decreased hepatic oxygenation and abnormal liver function (Liao et al, 2017). In this study, serum alkaline phosphatase, lactate dehydrogenase and creatinine activity in the affected Tibetan gazelles were significantly increased, which is consistent with phosphorus deficiency in pigs and cows (Drews et al, 2016;Zhang et al, 2017). Phosphorus deficiency should be differentiated from chronic fluorosis in mature animals (Kauv, 2017;Ferrier-Pagès et al, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…Previous investigations have demonstrated that phosphorus deficiency can induce a variety of functional and structural changes such as muscle weakness, decreased hepatic oxygenation and abnormal liver function (Liao et al, 2017). In this study, serum alkaline phosphatase, lactate dehydrogenase and creatinine activity in the affected Tibetan gazelles were significantly increased, which is consistent with phosphorus deficiency in pigs and cows (Drews et al, 2016;Zhang et al, 2017). Phosphorus deficiency should be differentiated from chronic fluorosis in mature animals (Kauv, 2017;Ferrier-Pagès et al, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…Accordingly, shifts in the Ca:P ratio in the blood are susceptible to dietary mineral status, while the Ca:P ratio in the bone reflects the stoichiometry of hydroxyapatite. With regard to serum ALP, the influence of P and Ca levels is discussed controversially (Sapir-Koren & Livshits, 2011;Euclydes Drews et al, 2016;Doige et al, 1975). The ALP with osteoblastic origin provides P for the mineralization of bones by the hydrolysis of pyrophosphate (Sapir-Koren & Livshits, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, an optimum Ca content was determined for piglets between 11 and 25 kg, at which an optimum bone ash content is achieved (González-Vega et al, 2016). An insufficient supply of the animals with P and Ca manifests in a deficient bone mineralization or in a loss of performance in body weight gain (BWG) (Adeola et al, 2015;Euclydes Drews et al, 2016;Rieger, 2017). Previous work has shown that this might also apply to an oversupply (Gerlinger et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphate is present in all cells of the body and is involved in almost all physiological chemical reactions. 21 Phosphate is also an important substance that makes Table 3. Multivariate regression analysis of the risk factors for 28-day mortality in patients (n ¼ 796) who participated in this study to determine the association between the serum phosphate level and the 28-day mortality risk of patients with septic acute kidney injury undergoing continuous renal replacement therapy (CRRT).…”
Section: Discussionmentioning
confidence: 99%